Strategi Memahami Teks Melalui Pembelajaran Bahasa Arab Qiraah Wa Tarjamah di MAN 1 Brebes - Afriyanto , Nurrokhmat; Fairuz Rosyid, M; Safii, Randi (ELOQUENCE : Journal of Foreign Language, 2023)
Background: The problem that arises in Arabic language learning carried out by MAN 1 Brebes is the difficulty of reading Arabic texts and translating them into three aspects, namely, linguistic aspects, non-linguistic aspects, and cultural aspects. Purpose: This study focused on Arabic language learning in MAN 1 Brebes. The main is the application of Qira’ah and Tarjamah methods. This method teaches Arabic grammar first and then translates. Method: This research uses a type of descriptive qualitative research. The data collected and analyzed is in the form of words and images and is not related to numbers. Results and Discussion: The strategies in qiroah learning used by MAN 1 Brebes teachers are: The first stage, qira’ah Jahriah or reading aloud, has a very high significance for first-level learning because this type focuses on practicing pronouncing vocabulary or letters correctly so that students understand between the sound of hijaiyyah letters and the symbol of the sound or hijaiyyah letters. The second stage is to read silently. In reading silently, students are trained to deepen the material. Students understand the meaning of words, the meaning of words within sentences, and the overall meaning of sentences in paragraphs. At the last stage in qiro’ah learning, the teacher analyzes the grammar in the qiroah reading text. This grammatical analysis is not only to understand the manuscript but also to strengthen the grammatical material that has been given previously. Conclusion and Implications: Qiro’ah teaching strategies with the Tarjamah grammar method in MAN 1 Brebes can be summed up into three categories: qiro’ah strategies, Tarjamah grammar methods, and learning techniques. The use of the Qiraah Wa Tarjamah strategy in Arabic language learning at MAN 1 Brebes effectively enhances students' text comprehension, making it advisable to be widely implemented with the development of teaching materials, teacher training, and appropriate evaluation.